METHODICAL AND ORGANIZATIONAL BASES OF BIOLOGICAL STABILITY OF AVIATION FUELS PROVIDING - Бойченко, С.; Безпальчук, О.; Шкільнюк, І. (Science-based technologies, 2012)
The research capacity of aviation fuels to biological damage. The mechanism of degradation of hydrocarbon aviation fuels and the consequences of this process. The methods of determining the presence of biological phases of aviation fuels. The efficiency of the basic methods of biological stability of aviation fuels. Methodical and organizational principles of biological stability of aviation fuels.